Islamic spirituality and social responsibility in curtailing the workplace deviance. Issue 4 (14th November 2016) - Bhatti, Omar Khalid; Alam, Muhammad Aftab; Hassan, Arif; Sulaiman, Mohamed
Abstract : Purpose: The current study aims to examine the relationship between Islamic spirituality (IS), Islamic social responsibility (ISR) and workplace deviance (WD). Design/methodology/approach: Data were collected from 400 Muslim employees of 9 business groups in Pakistan from manufacturing and services industry. The structure equation modeling was used to test the hypotheses, and the proposed model was assessed through renowned model fit indices. Findings: The findings revealed that IS and ISR help curtail WD. The study also provides empirical support to the hypotheses that employees with high levels of IS and social responsibility will tend to avoid deviant behavior at workplace. Originality/value: This study proposed IS and ISR as two possible stimuli that can help reduce employee deviant behavior at workplace. The findings of the present study revealed that IS, as well as ISR, is inversely related to WD. The present results augmented the existing body of knowledge regarding workplace spirituality in the field of organization behavior and further enriched the WD theory by offering new empirical relationships from an Islamic perspective.